Draft Annual Plan 1973-74 Part-II Appendices Government of Tripura - Planning Commission (Planning Commission, 1973)
Jhuming is yet a problem in the State and requires to be controlled in the interest of forest protection. But due to socio economics failure legal control has not been able to stop jhuming in the hills completely. As a measure of indirect control of shifting cultivation plantation under taungya system has been taken up by Forest Department which provides some monetary benefit to the tribal jhumias.
Government of Tripura, Development (Planning and Coordination) Department